2009
DOI: 10.2353/ajpath.2009.080727
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Regulates Androgen Receptor Expression and Prostate Cancer Growth

Abstract: Prostate cancers that progress during androgen-deprivation therapy often overexpress the androgen receptor (AR) and depend on AR signaling for growth. In most cases, increased AR expression occurs without gene amplification and may be due to altered transcriptional regulation. The transcription factor nuclear factor (NF)-B, which is implicated in tumorigenesis, functions as an important downstream substrate of mitogen-activated protein kinase, phosphatidylinositol 3-kinase, AKT, and protein kinase C and plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 41 publications
(52 reference statements)
7
115
3
Order By: Relevance
“…The consequences of Akt activation are mediated in part by activation of NF-kB signaling via stimulation of IKK (Dan et al 2008). Conversely, functional studies in mouse models and correlative studies in human prostate cancer have implicated deregulated NF-kB signaling in mediating androgen responsivity, metastasis, and disease outcome (Fradet et al 2004;Ismail et al 2004;Lessard et al 2006;Luo et al 2007;Zhang et al 2009). …”
Section: Signaling Pathways-akt/mtor and Mapk Signalingmentioning
confidence: 99%
“…The consequences of Akt activation are mediated in part by activation of NF-kB signaling via stimulation of IKK (Dan et al 2008). Conversely, functional studies in mouse models and correlative studies in human prostate cancer have implicated deregulated NF-kB signaling in mediating androgen responsivity, metastasis, and disease outcome (Fradet et al 2004;Ismail et al 2004;Lessard et al 2006;Luo et al 2007;Zhang et al 2009). …”
Section: Signaling Pathways-akt/mtor and Mapk Signalingmentioning
confidence: 99%
“…Previous studies have shown that PKB/Akt can activate NF-κB in castration-resistant PCa. 42,50,59 Therefore, we made an attempt to elucidate detailed mechanism and found that TPD52 interacts with p65 subunit of NF-κB that can regulate expression of genes associated with cell growth. From these results, it appears that upon phosphorylation of IkB after being dissociated from IkB, NF-κB p65 interacts with TPD52 in cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being implicated in ligand-independent AR activation and inducing expression of AR-regulated genes (85,86), NF-κB activation, in studies utilizing immunohistochemistry, is found more commonly in prostate cancer lymph node metastases than in localized tumors. In fact, NF-κB activation status in conjunction with…”
Section: Pathogenesis Of Androgen-independent Prostate Cancer (Aipc)mentioning
confidence: 99%
“…vFLIP has also been shown to activate the NF-κB (111) and JNK/AP-1 pathways, both of which induce cellular IL-6 expression (113,114). In the context of prostate cancer, increased NF-κB activity and cellular IL-6 signaling have both been shown to be ligandindependent activators of AR expression and transcriptional activity (81,85). Contrary to what we predicted, however, our results suggest that the androgen-independent phenotype induced by HHV-8 in LNCaP cells is independent of the AR signaling pathway.…”
Section: Hhv-8 Infection Increases Mapk Erk1/2 Activity Inmentioning
confidence: 99%